Pengaruh Risiko Bisnis, Struktur Aset dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Manufaktur Sektor Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia - ., Ratna Dewi; Mursidah, Mursidah Mursidah; Yunina, Yunina Yunina; Indrayani, Indrayani Indrayani (Jurnal Visioner & Strategis, 2024)
This study aims to examine the effect of business risk, asset structure, and profitability on capital structure in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The sample in this study consisted of 45 manufacturing companies in the consumer goods industry sector from 2019-2022. The data analysis method used multiple linear regression with the eviews version 10 tool. The results of the study indicate that business risk has a negative and significant effect while profitability has a positive and significant effect on capital structure in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. Then the asset structure does not have a significant effect on capital structure in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2022. Keywords    :  Business Risk, Assets Structure, Profitability,Capital Structure